2009
DOI: 10.1016/j.apsusc.2009.04.170
|View full text |Cite
|
Sign up to set email alerts
|

Argon-dominated plasma beam generated by filtered vacuum arc and its substrate etching

Abstract: A new technique to etch a substrate as a pre-treatment prior to functional film deposition was developed using a filtered vacuum arc plasma. An Ar-dominated plasma beam was generated from filtered carbon arc plasma by introducing appropriate flow rate of Ar gas in a T-shape filtered arc deposition (T-FAD) system. The radiation spectra emitted from the filtered plasma beam in front of a substrate table were measured. The substrate was etched by the Ar-dominated plasma beam. The principal results are summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The intensity of G peaks (I G ) peaks was in range ∼1565–1580 cm −1 and intensity of D peaks (I D ) was in the range ∼1345–1410 cm −1 . The results were consistent with the reported literatures .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The intensity of G peaks (I G ) peaks was in range ∼1565–1580 cm −1 and intensity of D peaks (I D ) was in the range ∼1345–1410 cm −1 . The results were consistent with the reported literatures .…”
Section: Resultssupporting
confidence: 93%
“…They reported the optimal adhesion, relationship between etching time, adhesion and film structure. Tanoue et al optimized surface level and roughness change as a function of Ar gas flow rate by cathodic arc plasma beam. Joes et al reported on basic research including effects of argon plasma pre‐treated substrate on structure, chemistry and delamination of DLC coated steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the deposition process of Cr layer was presumably still remained during the plasma treatment steps, leading to the interface to be a thin layer. Tanoue et al also reported the deposition process during the Ar‐dominated plasma condition . Moreover, the high substrate bias voltage in plasma treatment step led to the quick increase of substrate temperature, which would suspend the process owing to the temperature control.…”
Section: Resultsmentioning
confidence: 99%
“…The argon plasma etching technique was adopted to achieve surface finish of nanometer scale. The increase in etching rate with increase of argon flow rate was reported by Hideto Tanoue et al . Hence, the plasma etching rate with argon flow rate of 30, 40, 50, 70, and 90 sccm were evaluated at etching time of 10 min, bias voltage of 600 V, and current of 0.3 A.…”
Section: Experimental Designmentioning
confidence: 99%